Optimization of composite cryoprotectant for freeze-drying Bifidobacterium bifidum BB01 by response surface methodology - He Chen; Mengqi Tian; Li Chen; Xiuxiu Cui; Jiangpeng Meng; Guowei Shu (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Freeze drying has been well applied in the preparation of high-efficiency probiotic powders. However, the process is generally accompanied by probiotic viability deficiency, which is the bottleneck for further application. To improve the viability of Bifidobacterium bifidum BB01 during freeze-drying, we optimized the cryoprotectant of B. bifidum BB01 by response surface methodology (RSM) with a Central Composite Design (CCD). In this study, two values of B. bifidum BB01 with different protectant factors were investigated, including freeze-drying survival rate and the viable counts of per unit weight of freeze-dried powder. The optimized cryoprotectants were obtained as follows: glycine of 5.5%, sodium bicarbonate of 0.8%, xylo-oligosaccharides of 7%, arginine of 4.5% and skim milk of 25%. The survival rate and the viable counts of per unit weight of powder were 90.37 ± 1.9% and (2.78 ± 0.13) × 1011cfu·g−1, respectively, both close to the predicted value (88.58% and 2.71 × 1011 cfu·g−1). Our research demonstrated that RSM was successful in optimizing composite cryoprotectant for freeze-dried powder of B. bifidum which can as well protect the probiotic cells.